Interactions of the "piano-stool" [ruthenium(II)(η(6) -arene)(quinolone)Cl](+) complexes with water; DFT computational study - Zábojníková, Tereza; Cajzl, Radim; Kljun, Jakob; Chval, Zdeněk; Turel, Iztok; Burda, Jaroslav V (Journal of computational chemistry, 2016)
Full optimizations of stationary points along the reaction coordinate for the hydration of several quinolone Ru(II) half-sandwich complexes were performed in water environment using the B3PW91/6-31+G(d)/PCM/UAKS method. The role of diffuse functions (especially on oxygen) was found crucial for correct geometries along the reaction coordinate. Single-point (SP) calculations were performed at the B3LYP/6-311++G(2df,2pd)/DPCM/saled-UAKS level. In the first part, two possible reaction mechanisms-associative and dissociative were compared. It was found that the dissociative mechanism of the hydration process is kinetically slightly preferred. Another important conclusion concerns the reaction channels. It was found that substitution of chloride ligand (abbreviated in the text as dechlorination reaction) represents energetically and kinetically the most feasible pathway. In the second part the same hydration reaction was explored for reactivity comparison of the Ru(II)-complexes with several derivatives of nalidixic acid: cinoxacin, ofloxacin, and (thio)nalidixic acid. The hydration process is about four orders of magnitude faster in a basic solution compared to neutral/acidic environment with cinoxacin and nalidixic acid as the most reactive complexes in the former and latter environments, respectively. The explored hydration reaction is in all cases endergonic; nevertheless the endergonicity is substantially lower (by ∼6 kcal/mol) in basic environment. © 2016 Wiley Periodicals, Inc.
Keywords: DFT method; rate constants; thermodynamics; reaction mechanism; kinetics; Ru(II) piano-stool complex